The geopolitics of northern travels: Enactments of adventure and exploration in the Norwegian-Russian borderland - Wråkberg, Urban (Septentrio Academic Publishing, 2014)
Critical geopolitics is used in analysing discourses on a micro-social level in the performances and enactments taking place during fact-finding tours and leisure journeys in northernmost Europe. The cases of journeys focussed are those of Scandinavians travelling along, and sometimes departing from, the highway between the Norwegian village of Kirkenes and the Russian city of Murmansk. In travels undertaken for professional or leisure purposes alike a hyperreal meta-script is enacted mediated on the cosmopolitan cultural experiences held collectively by the travellers; simulacra provide the context for the enactments of fact-finding and drama taking place during border-passage. Three ways in which geopolitics enters travels in the northern borderland between Scandinavia and Russia are identified: scenarios of future regional developments, popularisations of research obsessed with any problems of bilateral relations, and what has been termed in this article the geopolitical anecdote. In considering the aesthetics of the simulations taking place in cross-border travels this study suggests focussing the meta-script of the American and the European road movie film genres. The essay argues that the cosmopolitan mind of any traveller, and its collective mediated content of cultural and political discourses, has been underestimated so far in the socio-political research regarding the borderlands of the European north.